The Effect of Emotional Maturity on Marriage Readiness in Generation Z - Nurul Pratiwi; Yulia Fitriani; Fathana Gina (Journal of Psychology and Social Sciences, 2026)
The trend of declining marriage rates and rising divorce rates has become a concern for individuals who are considering marriage. This highlights the importance of being prepared before entering married life. One factor that influences readiness for marriage is emotional maturity. Emotional maturity is viewed as an individual’s ability to manage, control, and express emotions appropriately. This study aims to determine the influence of emotional maturity on marriage readiness among Generation Z. The study involved 120 unmarried respondents aged 20–29 years in North Bekasi. A quantitative method using quota sampling was employed. Data collection was conducted online via Google Forms using instruments consisting of scales measuring emotional maturity and marriage readiness. The results show that emotional maturity has a positive and significant effect, contributing 22.6% to marriage readiness. The higher an individual’s level of emotional maturity, the higher their level of marriage readiness. Therefore, emotional maturity should be a key consideration when preparing individuals for marriage.